2008
DOI: 10.3354/ab00083
|View full text |Cite
|
Sign up to set email alerts
|

The invasive red alga Gracilaria vermiculophylla in the Baltic Sea: adaptation to brackish water may compensate for light limitation

Abstract: The recent introduction of Gracilaria vermiculophylla (Rhodophyta) to the Kiel Fjord area was a reason for concern, since this red macroalga perfoms best under mesohaline conditions and thus appears well adapted to thrive and spread in the Baltic Sea environment. A systematic survey on a coastal range of 500 km in 2006 and 2007 indicated considerable multiplication and spreading of G. vermiculophylla within Kiel Fjord, but provided little evidence of long-distance transport. Nonetheless, flow-through growth ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
90
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 38 publications
0
90
2
Order By: Relevance
“…Our findings suggest that G. vermiculophylla should generally be able to sustain positive growth in shallow Scandinavian estuaries during all seasons (except for the low saline parts (<5 PSU) of the Baltic Sea). This is in contrast to the findings of Weinberger et al (2008) who performed in situ experiments and found positive growth rates in G. vermiculophylla during the summer (high temperature and high light) but not during spring and autumn, when there was reduced light and temperature. However, biomass loss caused by mesoherbivores and fragmentation (potentially induced by the grazers) in the field experiment may explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our findings suggest that G. vermiculophylla should generally be able to sustain positive growth in shallow Scandinavian estuaries during all seasons (except for the low saline parts (<5 PSU) of the Baltic Sea). This is in contrast to the findings of Weinberger et al (2008) who performed in situ experiments and found positive growth rates in G. vermiculophylla during the summer (high temperature and high light) but not during spring and autumn, when there was reduced light and temperature. However, biomass loss caused by mesoherbivores and fragmentation (potentially induced by the grazers) in the field experiment may explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…However, biomass loss caused by mesoherbivores and fragmentation (potentially induced by the grazers) in the field experiment may explain this discrepancy. Indeed, Weinberger et al (2008) recorded higher grazing rates than were reported by Nejrup & Pedersen (2010). Low temperatures and ice cover (i.e.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The proposed scenario corresponds with the fact that Idotea baltica is virtually absent from Fucus vesiculosus in the German Baltic Sea and in winter, but not from other algae in the close vicinity of F. vesiculosus (Weinberger et al 2008). Since the presence of I. baltica alone is not sufficient to induce antifeeding defense, consumption is required (Rohde et al 2004) and an absence of consumption due to low palatability at low light conditions should result in no triggering of defense.…”
Section: Discussionmentioning
confidence: 99%